Experimental measurement and thermodynamic modeling of the solubility of carbon dioxide in aqueous blends of monoethanolamine and diethanolamine - Suleman, H. (American Institute of Physics Inc., 2017)
In this study, the solubilities of carbon dioxide in aqueous mixtures of monoethanolamine (MEA) and diethanolamine (DEA) were determined using a high pressure vapor-liquid equilibrium apparatus. The carbon dioxide loadings (mole of CO2/mole of amine mixture) were reported for a wide range of temperature (303.15, 323.15, 343.15 K) and pressure (100 - 4100 kPa). The carbon dioxide solubility shows an increase with increase in pressure and amine concentration and a decrease with increase in temperature in the aqueous blends of MEA and DEA. At carbon dioxide loadings above 1.0, the carbon dioxide solubility becomes a weak function of pressure and follows the general trend of carbon dioxide solubility in aqueous alkanolamines. The new experimental data points determined in this study were correlated by using a recently developed, enhanced Kent-Eisenberg model. An average absolute relative error of 9.4 was observed between the model results and experimental data, indicating good correlative capability of the thermodynamic model. © 2017 Author(s).